Proximal Tubule p53 in Cold Storage/Transplantation-Associated Kidney Injury and Renal Graft Dysfunction - Xiang, Xiaohong; Zhu, Jiefu; Zhang, Gang; Ma, Zhengwei; Livingston, Man J.; Dong, Zheng (Frontiers in Medicine, 2021)
Kidney injury associated with cold storage/transplantation is a primary factor for delayed graft function and poor outcome of renal transplants. p53 contributes to both ischemic and nephrotoxic kidney injury, but its involvement in kidney cold storage/transplantation is unclear. Here, we report that p53 in kidney proximal tubules plays a critical role in cold storage/transplantation kidney injury and inhibition of p53 can effectively improve the histology and function of transplanted kidneys. In a mouse kidney cold storage/transplantation model, we detected p53 accumulation in proximal tubules in a cold storage time-dependent manner, which correlated with tubular injury and cell death. Pifithrin-α, a pharmacologic p53 inhibitor, could reduce acute tubular injury, apoptosis and inflammation at 24 hours after cold storage/transplantation. Similar effects were shown by the ablation of p53 from proximal tubule cells. Notably, pifithrin-α also ameliorated kidney injury and improved the function of transplanted kidneys in 6 days when it became the sole life-supporting kidney in recipient mice. In vitro, cold storage followed by rewarming induced cell death in cultured proximal tubule cells, which was accompanied by p53 activation and suppressed by pifithrin-α and dominant-negative p53. Together, these results support a pathogenic role of p53 in cold storage/transplantation kidney injury and demonstrate the therapeutic potential of p53 inhibitors.